Dorsal CA1 lesions of the hippocampus impact mating tactics in prairie voles by shifting non-monogamous males’ use of space to resemble monogamous males - Sailer, Lindsay L.; Finton, Caitlyn J.; Patel, Pooja P.; Bogdanowicz, Steven M.; Ophir, Alexander G. (Frontiers in Behavioral Neuroscience, 2024)
Alternative mating tactics within mating systems are characterized by discrete patterns of spatio-temporal overlap with same- and opposite-sex conspecifics and mating-relevant outcomes. Socially monogamous “residents” maintain relatively small home range sizes, have territories that almost exclusively overlap with their mating partners, and are more likely to produce offspring than non-bonded “wandering” conspecifics. Because mating tactics appear to be so closely tied to patterns of space use, differences in spatial cognitive abilities might differentially impact individual male’s decisions to adopt a particular mating tactic and/or how efficient they are within their chosen mating tactic. Yet few studies have considered how the hippocampus, a brain region important for encoding cognitive maps and for processing contextual information, might impact how individuals adopt mating tactics or the spatio-temporal behaviors closely associated with them. We assessed the impact of lesions to the dorsal CA1 (dCA1) region of the hippocampus on male prairie vole space use, reproductive success, and mating tactics in semi-natural outdoor field conditions. Interestingly, dCA1 lesions did not impact the proportion of males that adopted resident or wandering mating tactics, and dCA1 lesions did not impact a male’s ability to form a pair bond in the lab. In contrast, we found that lesioning the dCA1 shifted the home range size of reproductively successful and unsuccessful males. Furthermore, we found that patterns of space use among residents were unaffected by dCA1 lesions, whereas wanderers with dCA1 lesions showed pronounced reductions of their space use habits and resembled non-lesioned residents. Collectively, our study supports the hypothesis that wanderer male prairie voles rely on dCA1-mediated spatial cognition to navigate their world in a way that resident males do not. Such differences might have implications of how individuals efficiently attract and defend mates, obtain resources, defend territories, and outcompete rivals.